High Burden of Antibiotic-Resistant Bacteria from Wastewater in Ethiopia: A Systematic Review - Asfaw T; Genetu D; Shenkute D (Dove Medical Press, 2020)
Tsegahun Asfaw, Deribew Genetu, Demissew Shenkute Department of Medical Laboratory Science, Debre Berhan University, Debre Birhan, North Shwa, EthiopiaCorrespondence: Tsegahun Asfaw P. Box: 445 Email tsegahun.asfaw12@gmail.comBackground: Currently, antibiotic-resistant bacteria (ARB) have become a serious global problem and considered as One Health challenge. Despite, wastewater contains a wide range of microbial pathogens and plays a significant role in the dissemination of ARB in the environment. However, it is the most overlooked in developing countries, particularly in Ethiopia.Methods: Different article searching devices like PubMed, Web of Science, Scopus, and Google Scholar were used to select research article by using the key terms. Hand search using a reference list is also used to retrieve the article. Preferred reporting items for systematic review and meta-analysis (PRISMA) guideline was used for literature search strategy, selection of publications, data extractions, and reporting result for the review process.Results: A total of seven original research articles were included from a total of 35,999 research articles obtained from the different searching techniques. The selected articles were used, the same study design and laboratory methods to isolate different types of resistant bacteria. All studies isolate pathogenic bacteria and highlighted the presence of resistant bacteria for multiple antibiotics.Conclusion: Multidrug resistance (MDR) bacteria were isolated from wastewater. This is an indication for the possible presence of pathogenic organisms that are discharged into the receiving environment probably waterbodies (lake and revers) posing risk to public health, animal, and environment. In Ethiopia the coverage of safe water supply is poor.  This obligated the society to use untreated water from rivers, lakes and others. The outlet of most urban sewage from hospital, hotels, and industries are directly running to those water bodies due to lack of proper wastewater management system.  Therefore ARB is a direct threat to those people that use those water bodies.Keywords: antibiotic resistance, antibiotic-resistant bacteria, wastewater, Ethiopia